2001
DOI: 10.1046/j.1365-3083.2001.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Dipeptidyl Peptidase IV (DP IV, CD26) Activity Abrogates Stress‐Induced, Cytokine‐Mediated Murine Abortions

Abstract: In the CBA × DBA/2 mouse model, stress‐triggered abortions are mediated by a Th1‐like cytokine response of decidual lymphocytes. The factors that determine the cytokine pattern leading to abortion are currently unknown. Dipeptidyl Peptidase IV (DP IV) enhances Th1‐cytokine responses and impairs the evolvement of a Th2 cytokine profile. The T‐cell‐activation antigen, CD26, possesses DP IV activity. The aim of the present study was to investigate the role of DP IV activity and CD26‐positive decidual lymphocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…This result confirms the notion of Th1 cytokines deleterious for pregnancy maintenance (21). Indeed, other Th1 cytokines, e.g., IFN-␥, increased after stress exposure in murine matings (23,50). Interestingly, Tangri and Raghupathy (51) demonstrated that the placenta of an abortionprone mating such as CBA/J ϫ DBA/2J produced high levels of TNF-␣ and IFN-␥, whereas in low abortion mating, e.g., CBA/J ϫ BALB/c, IL-10 is dominant.…”
Section: Cd8supporting
confidence: 86%
“…This result confirms the notion of Th1 cytokines deleterious for pregnancy maintenance (21). Indeed, other Th1 cytokines, e.g., IFN-␥, increased after stress exposure in murine matings (23,50). Interestingly, Tangri and Raghupathy (51) demonstrated that the placenta of an abortionprone mating such as CBA/J ϫ DBA/2J produced high levels of TNF-␣ and IFN-␥, whereas in low abortion mating, e.g., CBA/J ϫ BALB/c, IL-10 is dominant.…”
Section: Cd8supporting
confidence: 86%
“…The DPP IV inhibitors Ile-thiazolidide (2) and Ilepyrrolidine-2-nitrile abrogate stress-induced abortions and an enhanced production of interferon-γ in mice [273,274].…”
Section: Other Therapeutic Perspectivesmentioning
confidence: 99%
“…As most of the lymphocytes in endometrium and decidua are large granular lymphocytes, the absence of CD26 can be expected. Stress-triggered abortions are reported to be mediated by a Th1-like cytokine response of decidual lymphocytes, and CD26 is believed to enhance Th1 cytokine responses [37,38] . The presence of decidual CD26+ lymphocytes is reported in spontaneous abortions and, confusingly, also in normal pregnancy samples (but more prevalent in abortions), indicating a critical role for CD26 in pregnancy failure by inducing a Th1 local response [39,40] .…”
Section: Discussionmentioning
confidence: 99%